Sonographic evaluation of visceral and subcutaneous fat in obese children Avaliação ultrassonográfica da gordura visceral e subcutânea em crianças obesas - Sakuno T. (2014)
Objective: To evaluate sonographic measurements of visceral and subcutaneous fat in children, and to investigate the usefulness of preperitoneal fat (PF) and the abdominal wall fat index (AFI) as parameters to determine visceral fat and presence of nonalcoholic fatty liver disease (NAFLD) in obese children. Materials and Methods: A case-control study of a sample including 44 children (22 cases and 22 controls) matched by sex and age. The Student t test and the Fisher exact test were utilized in the descriptive and bivariate analysis. Results: The sonographic parameters evaluated - subcutaneous cell tissue, PF and intraperitoneal fat, and NAFLD - presented high statistical association with body mass index. NAFLD was observed in eight obese patients (36.36%), and PF and AFI were the variables with highest statistical significance, with p < 0.0001. Conclusion: Ultrasonography is useful tool in the differentiation and quantification of visceral and subcutaneous fat in children. The measures of PF and AFI are useful in the assessment of visceral fat and NAFLD in obese children. © Colégio Brasileiro de Radiologia e Diagnóstico por Imagem.